(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
A multipurpose plant setup is discussed using the concept of House Process and various other techniques to achieve objectives like reducing atmospheric CO2 to carbon and thus reduce global warming, production of hydrogen gas, to produce electricity, to provide energy feedback for improved effciency. These objectives are obtained by a six stage process. In the 1st stage atmospheric CO2 is absorbed using an improvised version of House Process. In the 2nd stage, CO2 is pro-duced by heating NaHCO3, a by-product of House Process. In the 3rd stage, reaction of the produced CO2 with Mg occurs, to get Magnesium Oxide and Carbon. The 4th stage consists of recovery of Mg from its oxide by using a modifed House Process and consequent electrolysis of MgCl2.The 5th stage, energy produced by the exothermic reactions is used to produce steam and produce electrical energy by rotating a turbine. Finally, hydrogen gas is produced by the reaction of steam and magnesium. Thus the various objectives are achieved. Key words: House Process; Modifed house process; Fuel cell; Multipurpose plant; Electric energy production; Hydrogen production; Capturing atmospheric CO2 DOI: 10.3126/hn.v6i0.4192 Hydro Nepal Vol 6, January 2010 Page : 38-41 Uploaded Date: 24 January, 2011